Passively switched cable-driven transmission for high-speed/high-force robot finger. (16th December 2016) - Phlernjai, M.; Takayama, T.; Omata, T.
Graphical Abstract: Abstract : This paper presents a novel cable-driven force magnification mechanism (FMM) that can passively switch from a high-speed (HS) phase to a high-force (HF) phase depending on the load. This is intended to provide an appropriate change in the reduction ratio in applications such as grasping with robotic or prosthetic hands. This mechanism uses only one actuator and does not require sensors to operate. Moreover, its stiffness remains low in the HS phase and increases sharply only after it enters the HF phase. This can result in a better impact tolerance during HS moves as opposed to continuously variable transmissions (CVTs), for which the stiffness increases proportionally. The developed prototype weighs 156 g and has dimensions of, excluding protruding parts. We used a simple 50 mm long cable-driven finger to demonstrate HS–HF two-phase grasping. The effects of the main design parameters were studied experimentally. For a selected configuration, the finger moved at an average joint speed of 372 deg/s in the HS phase and produced a fingertip force of 24.6 N in the HF phase. The compliant characteristics during an HS collision were examined and verified experimentally.